The Gut Microbiome on a Periodized Low-Protein Diet Is Associated With Improved Metabolic Health - Li, Zhencheng; Rasmussen, Torben Sølbeck; Rasmussen, Mette Line; Li, Jingwen; Henríquez Olguín, Carlos; Kot, Witold; Nielsen, Dennis Sandris; Jensen, Thomas Elbenhardt (Frontiers in Microbiology, 2019)
A periodized (14d on/14d off) 5% low protein-high carbohydrate (pLPHC) diet protects against weight gain, improves glucose tolerance in mice and interacts with concurrent voluntary activity wheel training on several parameters including weight maintenance and liver FGF21 secretion. The gut microbiome responds to both diet and exercise and may influence host metabolism. This study compared the cecal gut microbiome after a 13.5-week intervention study in mice on a variety of dietary interventions ± concurrent voluntary exercise training in activity wheels. The diets included chronic chow diet, LPHC diet, 40 E% high protein-low carbohydrate (HPLC) diet, an obesigenic chronic high-fat diet (HFD) and the pLPHC diet. Our hypothesis was that the gut microbiome changes with pLPHC diet would generally reflect the improved metabolic health of the host and interact with concurrent exercise training. The gut microbiome analyses revealed greater abundance phylum Bacteroidetes and the genus Akkermansia on chronic and periodized LPHC and higher abundance of Oscillospira and Oscillibacter on HFD. These diet-induced gut microbiome changes correlated strongly with the differences in a range of host metabolic health-measures. In contrast, no significant effect of concurrent exercise training was observed. In conclusion, pLPHC diet elicits substantial changes in the gut microbiome. In contrast, only subtle and non-significant effect of concurrent activity wheel exercise were observed. The pLPHC-associated microbiome changes may contribute to the healthier host phenotype observed in these mice.